2021
DOI: 10.1155/2021/9964852
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Numerical Analysis Study on Loess‐Lime Structures Used for Lateral Antiseepage in Deep Collapsible Ground Embankment

Abstract: The focus of this study was to investigate the effect of loess soil treated with lime on the lateral-seepage response. Three groups of box experiments were carried out to study the lateral-seepage effect under different types of loess-lime structures. Automated testing systems were designed to perform experiments and collect data. Additionally, numerical analysis of lateral-seepage impact and embankment settlement was performed. Finally, moisture content and settlement were monitored to quantify lateral-seepag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 21 publications
2
8
0
Order By: Relevance
“…Equation (6) calculates the linear output in which and stand for interconnection weights and input signals in the -th layer, respectively [ 39 , 40 ]: where means the number of neurons in the layer. Regarding scientific applications of deep learning methods [ 51 , 52 , 53 , 54 , 55 , 56 , 57 ], we applied the MSE loss function, as shown in Figure 4 . Noting that, we randomly split the data into training datasets (80%), validation datasets (10%), and testing datasets (10%).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Equation (6) calculates the linear output in which and stand for interconnection weights and input signals in the -th layer, respectively [ 39 , 40 ]: where means the number of neurons in the layer. Regarding scientific applications of deep learning methods [ 51 , 52 , 53 , 54 , 55 , 56 , 57 ], we applied the MSE loss function, as shown in Figure 4 . Noting that, we randomly split the data into training datasets (80%), validation datasets (10%), and testing datasets (10%).…”
Section: Resultsmentioning
confidence: 99%
“…where N means the number of neurons in the (l − 1) − th layer. Regarding scientific applications of deep learning methods [51][52][53][54][55][56][57], we applied the MSE loss function, as shown in Figure 4. Noting that, we randomly split the data into training datasets (80%), validation datasets (10%), and testing datasets (10%).…”
Section: 𝑅𝑒𝐿𝑈(𝑥) = {mentioning
confidence: 99%
“…As quicklime releases a lot of heat energy during digestion, this process accelerates the hardening of lime soil. In contrast, the permeability coefficient is relatively small [ 14 ]. P.C.32.5 composite Portland cement produced by Qilian Mountain Cement Group in Gansu province is used in this study.…”
Section: Methodsmentioning
confidence: 99%
“…Piotr Kanty conducted over 100 compressions and a dozen tension tests to study cement-fly ash-modified soil’s compression and tensile strength [ 13 ]. Zhang Zhengrui et al [ 14 ] studied the lateral seepage control of roadbeds using a lime soil compaction pile and continuous wall. The experiment found modified loess using lime for seepage prevention on a deep collapsible loess embankment slope.…”
Section: Introductionmentioning
confidence: 99%
“…It has a certain bearing capacity in the dry state, but the cementation point between the particle skeleton will dissolve when it encounters water. Zhang Zhengrui et al [3][4] conducted a study on the seepage prevention of lime-modified loess on the embankment slope of deep collapsible loess. They found that lime piles and lime seepage prevention walls have good performance as transverse seepage prevention structures, and the performance of lime pile seepage prevention walls is better than that of lime compacted piles.…”
Section: Introductionmentioning
confidence: 99%